Hypochondria among health sector works under shadow Corona pandemic covid-19: Empirical Study in the state of Laghouat - KOUIDRI, Aloi; ADJEB, Boumediene (Journal of Human Sciences, 2022)
The current study aimed to know the differences in the level of Hypochondria due to the gender variable and the variable of profession among a sample of workers in the health sector in Laghouat, and to achieve the objectives of the study, the Minnesota Multiphasic Personality Inventory (MMPI-2) was used to measure the Hypochondria. .In the basic study based on the descriptive approach, the study was applied to a random sample of workers in the health sector, amounting to 110 workers. The study yielded the following result: -There are differences in the level of Hypochondria due to the gender variable in the total sample for females - There are differences in the level of Hypochondria due to the variable of profession among the total sample in favor of the nurses sample.